Comparison of attitudes and learning methods towards statistics in NBS between undergraduates and postgraduates. - Phua, Wee Leng. (2008)
This main aim of this study is to compare the differences in statistical attitudes and learning methods between Undergraduates and Postgraduates. Underlying factors for the statistical attitudes include internal, external, demographics and learning methods. We also seek to find out how attitudes affect learning methods.